2015
DOI: 10.1111/dmcn.12839
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the Dutch‐language version of the Communication Function Classification System and its association with language comprehension and method of communication

Abstract: AIM The aims of this study were to determine the intra-and interrater reliability of the Dutchlanguage version of the Communication Function Classification System (CFCS-NL) and to investigate the association between the CFCS level and (1) spoken language comprehension and (2) preferred method of communication in children with cerebral palsy (CP). , recruited from rehabilitation centres throughout the Netherlands. Because some centres only contributed to part of the study, different numbers of participants are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 25 publications
(50 reference statements)
1
31
0
Order By: Relevance
“…In a study by van der Zwart, CFCS and GMFCS were moderately correlated10 ) . In addition, the communication performance was strongly correlated with the level of spoken comprehension and methods of communication.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In a study by van der Zwart, CFCS and GMFCS were moderately correlated10 ) . In addition, the communication performance was strongly correlated with the level of spoken comprehension and methods of communication.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the communication performance was strongly correlated with the level of spoken comprehension and methods of communication. They concluded that the method of communication, such as verbal and nonverbal communication and the level of spoken language of a child with CP, were most strongly related to everyday communication performance10 ) . Our study did not investigate this relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the CFCS had good test-retest reliability and professional inter-rater reliability, with slightly less parent-professional inter-rater reliability [22]. The CFCS has been translated into Dutch and Farsi and these measures have also demonstrated good reliability [23,24]. …”
Section: Classification Measuresmentioning
confidence: 99%
“…In addition to exploring the validity of a Dutch version of the CFCS, the article by Vander Zwart et al 4 attempts to tease out some of the factors that contribute to the composite level of function. The advantage conferred by intelligible speech is clearly seen when focusing on a child's ability to communicate effectively with unfamiliar partners.…”
mentioning
confidence: 99%